192 Do health gains match investment in post partum haemorrhage prevention and care? Lessons learned from two French programs, Sphere and Pithagore 6. (23rd September 2015) - Bouvier-Colle, M H; Deneux-Tharaux, C; Dupont, C; Dreyfus, M; Rudigoz, R C; ,; ,
Abstract : Post partum haemorrhage (PPH) is the most common obstetric complication at delivery and a major cause of maternal death worldwide. In France, PPH remains the primary cause resulting in a maternal mortality ratio of 2.4 per 100 000 live births vs less than 1 per 100 000 in the UK. Ten years ago, the National committee of medical experts on maternal mortality draw the attention of the clinicians on the substandard care found in 80% of the maternal deaths due to PPH. Such substandard care was also observed in a survey on severe PPH (2001) where clinical audit was used. Finally the HAS with the CNGOF published in 2004 their Recommendations for clinical practices related to PPH. In parallel, two teams of clinicians very aware of that poor situation launched actions associated with evaluative research studies. The first team was lead by M Dreyfus in the Basse Normandie region and the other was managed by RC Rudigoz à Lyon. The Sphere and the Pithagore6 programs were similar in their final goal, which is to decrease the severe PPH incidence, but they differed in their methods. Our objectives are to present these two programs, and to show a synthesis of the lessons learnt. Both programmes targeted the practices for management of PPH. They used the same definitions of clinically diagnosed PPH and of severe PPH, presence of one or more of the following criteria: blood transfusion, arterial ligation or embolisation or uterine surgery, hysterectomy, peripartum haemoglobin delta of 4 g/dl or more, and maternal death. Their programs, a multifaceted intervention in which recommended procedures were in total agreement with the HAS–CNGOF recommendations, were implemented differently. In Sphere, the intervention combined the collective design and active dissemination of clinical guidelines, the involvement of local opinion leaders, the use of paper reminders, the centralised purchase of blood collecting bags for precise evaluation of PPH and the organisation of an easy system for transfer to the unique regional unit of embolisation. It was implemented in the perinatal network of Basse Normandie between February 2003 and March 2004. The evaluative protocol of research was a before (2002)/after (2005) survey, comparing samples of deliveries and PPH, and the totality of the severe PPH. Data were retrospectively collected. In Pithagore 6, a cluster randomised trial was carried out in six perinatal networks. The intervention will be presented. The main features were a simple reminder of the clinical rules in each maternity unit of the reference arm, and a multifaceted program in the intervention arm. The mean rates of severe PPH were 0.86% in 2005 for Sphere (0.8% in 2002) and 1.6% for Pithagore 6. PPH-related preventive practices improved significantly in both programs. The initial PPH management did not change significantly, except the mean delay for sulprostone administration in persistent atony. The absence of reduction in the rate of severe PPH with both interventions disappointed the clinicians a lot, and contrasted with results published by Althabe. But the initial incidence levels were already low in France and extremely high in Latin America and a constant increase of the cesarean deliveries which augment the risk of severe PPH. Some clinical practices significantly improved in both programs which conception and methods varied suggesting that the HAS/CNGOF recommendations related to PPH might have been underway. The prevention, diagnosis and treatment of PPH is a very interesting model of all the difficulties one can encounter to measure the effects of clinical intervention, because the recognition of the disease and the appreciation of severity depend directly on the capacity of the professionals while the correction of the complication depends on the availability of the services. Some French doctors resist in changing their practices even with evidence-based clinical results. In the hypothesis of a current change in their clinical practices it would be important also to measure their effect on the health status of the population with a more accurate tool. L'hémorragie du post partum (HPP) est la plus répandue des complications obstétricales au cours de l'accouchement et la principale cause de mortalité maternelle dans le monde. En France, l'HPP demeure la 1ère cause avec un taux de 2, 4 pour 100 000 naissances vivantes contre 1, 0 au Royaume Uni. Il y a dix ans, le Comité national d'experts sur la mortalité maternelle attirait l'attention des cliniciens sur les soins non optimaux qui expliquaient 80% des décès maternels dûs aux HPP. Des soins non optimaux des PPH sévères furent également mis en évidence dans une étude, qui mettait en oeuvre un audit clinique (2001). Enfin, l'HAS et le CNGOFpublièrent en 2004 des recommandations pour la prise en charge des PPH. Parallèlement, deux équipes de cliniciens préoccupés du problème, lancèrent des interventions associées à une évaluation scientifique. La première équipe était dirigée par M Dreyfus en Basse-Normandie et la seconde par RC Rudigoz à Lyon. Les programmes Sphère et Pithagore6 partageaient les mêmes buts, diminuer l'incidence des PPH sévères, mais différaient dans leur stratégie. Notre objectif est de présenter ces deux programmes et de faire la synthèse des leçons qui en ressortent car ils aboutissent à des résultats similaires. Les deux programmes visaient les pratiques cliniques de traitement des HPP. Ils adoptaient la même définition de l'HPP, définition clinique, et de l'HPP sévère, présence d'un ou plusieurs des critères suivants, transfusion de sang, ligature ou embolisation des artères, chirurgie, hystérectomie, delta peripartum d'hémoglobine ≥ 4 g/dl ou décès maternel. Leurs programmes, intervention multifacette, dont les règles de pratique clinique étaient celles du HAS/CNGOF, furent gérés différemment. Sphère combinait une conception et dissémination collective des guides de prise en charge, l'implication des personnalités chefs de file, l'utilisation de rappels écrits, l'achat centralisé des sacs collecteurs de sang pour l'évaluation précise de l'HPP et la facilitation du transfert vers l'unique unité régionale d'embolisation. Le programme fut implanté entre février 2003 et mard 2004, au sein du réseau périnatal de Basse-Normandie. L'évaluation scientifique reposait sur une étude avant (2002)/après (2005) qui comparait des échantillons de naissances et de PPH et la totalité des HPP sévères. La collecte des données était rétrospective. Pithagore6 était un essai randomisé en grappe, appliqué dans 6 réseaux périnatals. Les détails de l'intervention seront présentés. Les faits principaux étaient un simple rappel des bonnes pratiques dans chaque maternité du bras témoin, et un programme multifacette dans le bras intervention. Les taux moyens d'HPP sévère étaient 0, 86% en 2005 dans Sphère (0, 8 en 2002) et 1, 6% dans Pithagore6. Les gestes préventifs de l'HPP augmentèrent significativement dans les deux programmes:administration prophylactique d'ocytocine. La prise en charge initiale de l'HPP ne changea pas significativement à l'exception du délai d'administration de la sulprostone dans l'atonie persistante. L'absence de preuve d'une réduction de l'HPP sévère dans les deux interventions a vraiment déçu les cliniciens et contraste avec des résultats publiés par Althabe. Mais les niveaux de départ de l'incidence étaient déjà bas en France et extrêmement élevés en Amérique latine, de plus associés à un accroissement constant de l'accouchement par césarienne qui augmente le risque d'HPP sévère. Quelques pratiques cliniques ont évolué significativement dans les deux programmes suggérant que la notoriété des recommandations du CNGOF/HAS était à l'oeuvre. La prévention, le diagnostic et le traitement des HPP constituent un modèle intéressant des difficultés rencontrées pour mesurer les effets d'une intervention clinique, car la reconnaissance de la maladie et l'appréciation de sa sévérité sont directement liées à la compétence des professionnels tandis que la résolution de la complication dépend aussi de la disponibilité des équipements. En France, les médecins résistent au changement de leurs pratiques malgré des preuves scientifiques sérieuses. Dans l'hypothèse d'un changement consenti de leurs pratiques cliniques, il serait tout aussi important d'en mesurer les effets sur la santé des populations d'une manière systématique et précise.